2011
DOI: 10.1074/jbc.m110.217711
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Calcium Uptake Regulates Rapid Calcium Transients in Skeletal Muscle during Excitation-Contraction (E-C) Coupling

Abstract: Defective coupling between sarcoplasmic reticulum and mitochondria during control of intracellular Ca 2؉ signaling has been implicated in the progression of neuromuscular diseases. Our previous study showed that skeletal muscles derived from an amyotrophic lateral sclerosis (ALS) mouse model displayed segmental loss of mitochondrial function that was coupled with elevated and uncontrolled sarcoplasmic reticulum Ca 2؉ release activity. The localized mitochondrial defect in the ALS muscle allows for examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 44 publications
7
109
7
Order By: Relevance
“…In another knock-in mouse model of MH, RyR1(R163C), bioenergetics defects, including elevated [Ca 2+ ] m and ROS, and decreased oxidative phosphorylation have been reported (Giulivi et al, 2011). These results imply that there is a Zhou et al, 2010;Yi et al, 2011) Duchenne muscular dystrophy (dystrophin mutations) Robert et al, 2001a;Shkryl et al, 2009;Bellinger et al, 2009;Millay et al, 2008;Goonasekera et al, 2011 (Chang et al, 2012) Smooth muscle atrophy (CSQ-1 knockout) (Paolini et al, 2007) Aging and/or sarcopenia (RyR1, b-amyloid) Boncompagni et al, 2012) n.d., not determined.…”
Section: Ros As Regulatory Signaling Factors In Cardiac and Skeletal mentioning
confidence: 72%
See 1 more Smart Citation
“…In another knock-in mouse model of MH, RyR1(R163C), bioenergetics defects, including elevated [Ca 2+ ] m and ROS, and decreased oxidative phosphorylation have been reported (Giulivi et al, 2011). These results imply that there is a Zhou et al, 2010;Yi et al, 2011) Duchenne muscular dystrophy (dystrophin mutations) Robert et al, 2001a;Shkryl et al, 2009;Bellinger et al, 2009;Millay et al, 2008;Goonasekera et al, 2011 (Chang et al, 2012) Smooth muscle atrophy (CSQ-1 knockout) (Paolini et al, 2007) Aging and/or sarcopenia (RyR1, b-amyloid) Boncompagni et al, 2012) n.d., not determined.…”
Section: Ros As Regulatory Signaling Factors In Cardiac and Skeletal mentioning
confidence: 72%
“…However, Ca 2+ waves propagate throughout the muscle fibers upon inhibition of mitochondrial Ca 2+ uptake by an uncoupler or Ru360 (Zhou et al, 2010). Furthermore, in the regions of depolarized mitochondria, [Ca 2+ ] c signals that are associated with depolarization-induced excitation-contraction (EC) coupling are increased, whereas the amplitude of the [Ca 2+ ] m transients is decreased (Yi et al, 2011). These data indicate that SOD1 mutations might cause mitochondrial injury that leads to a local dysregulation of EC coupling.…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…These defects were observed in 37-day-old presymptomatic mice as well as in symptomatic mice at 3-4 mo (ϳ90 -120 days) of age, suggesting that these changes in the muscle fiber occur before there is evidence of muscle force loss. More recently, decreased cytosolic Ca 2ϩ buffering by mitochondria was observed in these regions during patch-clamped membrane depolarization (35). This further suggests that primary defects in the muscle fiber are associated with altered intracellular Ca 2ϩ signaling.…”
mentioning
confidence: 96%
“…by the mitochondrial Ca 2? uniporter (MCU), rapid uptake (RaM) and mitochondrial RyR (mRyR) mechanisms, the first one being the most important in skeletal muscle (Rudolf et al 2004;Brookes et al 2004;Ryu et al 2010;Yi et al 2011;Pizzo et al 2012).…”
Section: Mitochondria and Ncx Functionmentioning
confidence: 99%
“…transients described above, but this is far from clear: some authors proposed that mitochondria may be relevant only in slow-twitch fibres (Sembrovich et al 1985;Gillis 1997), but others have reported mitochondrial Ca 2? uptake after single and tetanic stimulation (Rudolf et al 2004;Yi et al 2011;Scorzeto et al 2013) and altered kinetics in single Ca 2? transients after poisoning the mitochondria in mouse fast twitch muscles.…”
Section: Introductionmentioning
confidence: 99%